The Mobile Singing Software of Technology in the Study of the Influence of Vocal Music Teaching on College Students’ Achievement - Gao, Yuan; Li, Changhan (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: The study investigates the impact of WeSing, a mobile singing application, on the vocal music achievement of sophomore students majoring in vocal performance at the Kunming University of Communication. Traditional vocal training in China, which heavily relies on repetitive piano-accompanied practice, often lacks diversity. To address these limitations, this research explores whether integrating WeSing into vocal training can enhance students’ academic performance. Materials and Methods: The study utilized a quasi-experimental design with a quantitative research approach. Participants included 80 students from two classes taught by the researcher, with 40 students in each class. One class served as the experimental group, incorporating WeSing into their training over eight weeks, while the control group continued with traditional methods. Three industry experts evaluated the participants based on the university’s official scoring criteria, aligned with institutional rules and guidelines. The criteria encompassed five key performance variables: musical integrity, performer expressiveness, breathing techniques, pitch accuracy, and rhythm. Pretest and post-test score differences for each variable were calculated and analyzed using independent samples t-tests to compare the experimental and control groups. Results: The performance of the experimental group was significantly better than that of the control group. WeSing had a positive impact on students’ academic achievements, especially in terms of musical integrity and performance expressiveness. This highlights the potential of WeSing’s AI-driven functions in complementing traditional teaching methods and promoting the modernization of vocal music education in China. Conclusion: The research results show that WeSing has a positive impact on the academic performance of vocal music students. The improvement is not only reflected in aspects such as musical integrity, performer’s expressiveness, breathing for singing, rhythm, and pitch accuracy, but also indicates that technological intervention enriches students’ learning methods, encourages self-updating, and cultivates autonomous learning ability and independent thinking ability. This new research highlights the advantages of innovative teaching models, promotes the formation of personalized and interactive teaching, and verifies the value of technology-assisted teaching. The flexible learning paths provided by WeSing meet the needs and habits of different students, offering a new direction for vocal music teaching and helping to cultivate more outstanding vocal music talents.